2019
DOI: 10.3389/fphar.2019.00382
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 as a Potential Mediator of Cardiovascular Risk in Metabolic Diseases

Abstract: Free radicals act as secondary messengers, modulating a number of important biological processes, including gene expression, ion mobilization in transport systems, protein interactions and enzymatic functions, cell growth, cell cycle, redox homeostasis, among others. In the cardiovascular system, the physiological generation of free radicals ensures the integrity and function of cardiomyocytes, endothelial cells, and adjacent smooth muscle cells. In physiological conditions, there is a balance between free rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
107
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(122 citation statements)
references
References 123 publications
(128 reference statements)
0
107
0
2
Order By: Relevance
“…Taken together, these outcomes indicate that cocoa diet avoids diabetes‐induced depletion of Nrf2 and their antioxidants enzymes, mainly MT, contributing to prevent oxidative stress and vascular injury in diabetic rats. Although the role of Nrf2 in diabetes is not fully understood, it has been indicated that decreased Nrf2 activity in arteries contributes to oxidative stress and favours vascular remodeling and dysfunction in diabetes . Accordingly, the increase of Nrf2 activity by several activators has been considered as a promising approach for preventing the development of vascular complications in diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these outcomes indicate that cocoa diet avoids diabetes‐induced depletion of Nrf2 and their antioxidants enzymes, mainly MT, contributing to prevent oxidative stress and vascular injury in diabetic rats. Although the role of Nrf2 in diabetes is not fully understood, it has been indicated that decreased Nrf2 activity in arteries contributes to oxidative stress and favours vascular remodeling and dysfunction in diabetes . Accordingly, the increase of Nrf2 activity by several activators has been considered as a promising approach for preventing the development of vascular complications in diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the consequences of DNA damage, including growth arrest, cell senescence, and apoptosis, are all increased in plaque microenvironment and their levels are correlated with increased severity of atherosclerosis . Additionally, the Nrf2, which controls the expression of antioxidant response element‐dependent genes to regulate cellular resistance to oxidants, is an universal guardian against oxidative and electrophilic stresses induced by toxicants in human organs and/or tissues, especially for cardiovascular system, and a key marker for cellular oxidative stress . Intriguingly, altered expression of Nrf2 is also associated with atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Additionally, the Nrf2, which controls the expression of antioxidant response element-dependent genes to regulate cellular resistance to oxidants, is an universal guardian against oxidative and electrophilic stresses induced by toxicants in human organs and/or tissues, especially for cardiovascular system, and a key marker for cellular oxidative stress. 45,46 Intriguingly, altered expression of Nrf2 is also associated with atherosclerosis. 55 In the present study, the results showed that these TiO 2 -NPs could elicit a significant increase of DNA damage and MN frequency in HUVECs in culture (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations